2009
DOI: 10.2478/s10059-009-0029-8
|View full text |Cite
|
Sign up to set email alerts
|

Type D personality in Poland: Validity and application of the Polish DS14

Abstract: Type D personality (increased negative emotions paired with emotional non-expression) is an emerging risk indicator

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 30 publications
6
30
1
3
Order By: Relevance
“…Research on the prevalence of Type D personality in the Polish population showed that 9.3% of healthy individuals [16] and 34.8% in the general population [10] present type D personality, while the percentage of cardiac patients was 72, 1% [10]. In a study conducted by our team, the proportion of patients with Type D personality was lower and amounted to 52%.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Research on the prevalence of Type D personality in the Polish population showed that 9.3% of healthy individuals [16] and 34.8% in the general population [10] present type D personality, while the percentage of cardiac patients was 72, 1% [10]. In a study conducted by our team, the proportion of patients with Type D personality was lower and amounted to 52%.…”
Section: Discussionmentioning
confidence: 79%
“…The presence of type D personality traits was assessed by the DS14 developed by Denollet [9] and adapted to Polish conditions by Ogińska-Bulik and Juczyński [10]. The questionnaire consists of 14 items, of which seven measures the tendency to experience negative emotions and the remaining seven -the tendency to avoid expressing these emotions and related behaviors (Social Inhibition).…”
Section: Methodsmentioning
confidence: 99%
“…The result corresponds to the value of the 4 th sten, according to the standards established for SPP-25 [27]. The mean results of type D personality dimensions were higher than the means obtained in the standardization tests conducted among the healthy adults [41]. According to the adopted criteria, type D personality is determined by a score of at least 10 points simultaneously, which was obtained by 55 (53.9%) of our respondents.…”
Section: Wynikimentioning
confidence: 70%
“…The Type D Scale (DS-14) authored by Denollet [12] has been adapted to the Polish setting by Ogińska-Bulik, Juczyński and Denollet [41]. The scale consists of 14 statements, 7 of which relate to negative emotionality and 7 to social inhibition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation